Impact Of Scale Build-Up Models On Energy Utilization In Heat Exchangers - Duffuaa, S. O. (2020)
In this paper an energy utilization index is presented. It is used to investigate the impact of scale build-up in heat exchange equipment. The investigation is carried out using several scale build-up models. The models employed in this paper are the linear, logarithmic, and the asymptotic one. It has been demonstrated by a realistic example that the type of scale build-up model assumed greatly affects energy utilization and maintenance scheduling for heat exchange equipment. Copyright (C) 1999 John Wiley Sons, Ltd.